Ghrelin reduces liver impairment in a model of concanavalin A-induced acute hepatitis in mice - Mao YQ; Wang JB; Yu FJ; Cheng J; Li HQ; Guo CY; Fan XM (Dove Medical Press, 2015)
Yuqing Mao,1 Jianbo Wang,2 Fujun Yu,1 Jian Cheng,1 Huanqing Li,1 Chuanyong Guo,3 Xiaoming Fan11Department of Gastroenterology and Hepatology, Jinshan Hospital of Fudan University, Shanghai, 2Department of Gastroenterology and Hepatology, The Central Hospital of Lishui City, Wenzhou Medical University, Zhejiang, 3Department of Gastroenterology and Hepatology, Shanghai Tenth People’s Hospital of Tongji University, Shanghai, People’s Republic of ChinaBackground and aims: Ghrelin is a 28-amino-acid gut hormone that was first discovered as a potent growth hormone secretagogue. Recently, it has been shown to exert a strong anti-inflammatory effect. The purpose of the study reported here was to explore the effect and mechanism of ghrelin on concanavalin (Con) A-induced acute hepatitis.Methods: Balb/C mice were divided into four groups: normal control (NC) (mice injected with vehicle [saline]); Con A (25 mg/kg); Con A + 10 µg/kg ghrelin; and Con A + 50 µg/kg ghrelin (1 hour before Con A injection). Pro-inflammatory cytokine levels were detected. Protein levels of phosphoinositide 3-kinase (PI3K); phosphorylated Akt (p-Akt); caspase 3, 8, and 9; and microtubule-associated protein 1 light chain 3 (LC3) were also detected. Perifosine (25 mM) (an Akt inhibitor) was used to investigate whether the protective effect of ghrelin was interrupted by an Akt inhibitor. Protein levels of p-AKT; Bcl-2; Bax; and caspase 3, 8, and 9 were also detected.Results: Aspartate aminotransferase, alanine aminotransferase, and pathological damage were significantly ameliorated by ghrelin pretreatment in Con A-induced hepatitis. Inflammatory cytokines were significantly reduced by ghrelin pretreatment. Bcl-2; Bax; and caspase 3, 8, and 9 expression were also clearly affected by ghrelin pretreatment, compared with the Con A-treated group. However, the Akt kinase inhibitor reversed the decrease of Bax and caspase 3, 8, 9, and reduced the protein level of p-Akt and Bcl-2. Ghrelin activated the PI3K/Akt/Bcl-2 pathway and inhibited activation of autophagy.Conclusion: Our results demonstrate that ghrelin attenuates Con A-induced acute immune hepatitis by activating the PI3K/Akt pathway and inhibiting the process of autophagy, which might be related to inhibition of inflammatory cytokine release, and prevention of hepatocyte apoptosis. These effects could be interrupted by an Akt kinase inhibitor.Keywords: PI3K/Akt pathway, autophagy, inflammation, apoptosis